EXPLORING THE POTENTIAL OF HERBAL THERAPY IN COVID-19 - DESAI, HARITA; MHATRE, ADITYA; SINGH, RASHMI; LOKHANDE, GAURI; KONDHARE, ASHWINI; BUNDAKE, SAKSHI (International Journal of Current Pharmaceutical Research, 2023)
The world has been facing the deadly coronavirus for a stretch of period now and with the innovation and latest research, the development of vaccines has been possible. The initial duration wherein the vaccines were under trials the most opted choice was the use of modern drug like Remdesivir along with other existing daily supplements. This review article describes the various pathogenic mechanism of action by which the virus attacks and replicates inside the body. It briefly gives the role of modern allopathy drugs, the use of traditional Ayurvedic medicines and herbs which act by discrete mechanism. It also focuses on the traditional herbs acting as drugs and supplements which could be prophylactic and hence used for the management of mild to moderate COVID conditions. Herbal agents like Ocimum sanctum, Curcuma longa, Withaniasomnifera, Glycyrrhiza glabra, Andrographis paniculata, Zingiber officinale etc. can have different antiviral actions which were used during the COVID-19 outbreak and have shown good margin of efficacy. Phytoconstituents like quercetin, fenugreek, liquorice etc. have shown to have activities like anti-viral, anti-inflammatory, immunomodulatory action, which is studied further in in silico modelling and by molecular docking. The significant use of these herbs and phytoconstituents which have contributed for preventive action has been described.